Kemampuan Tumbuhan Typha Angustifolia Dalam Sistem Subsurface Flow Constructed Wetland Untuk Pengolahan Limbah Cair Industri Kerupuk (Studi Kasus Limbah Cair Sentra Industri Kerupuk Desa Kenanga Kecamatan Sindang Kabupaten Indramayu Jawa Barat) - Abdulgani, Hamdani; Izzati, Munifatul; S, Sudarno (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Industrial crackers centers at Kenanga Village has been able to lift the local economy,but that has been polluting the surrounding surface water contamination caused by wastewater discharged directly without any treatment in advance so that the water is black and smells foul . Therefore, the need of alternative wastewater treatment and in the study conducted by the artificial wetlands (constructed wetland) system Sub - surface Flow vertical flow with Typha angustifolia plant and use a medium sized sand 1 mm - 5 mm were previously washed first with media thickness of 30 cm and then operated intermittently using a peristaltic pump 6 times a day with the design of constructed wetlands construction made of wood coated with plastic and reactor dimensions 90 cm x 45 cm x 50 cm . As for the control (no treatment) using use the bucket size diameter 40 cm and height of 20 cm. This study aims to determine the ability of Subsurface Flow Constructed Wetland with Typha angustifolia plants in lowering the concentration of TSS , BOD5 , COD , ammonia (NH3 – N) and sulfide (H2S) at 5,10 and 15 days of processing . The results showed a decrease in the concentration efficiency at consecutive time 5 , 10 and 15 days in Subsurface Flow Constructed wetland with Typha angustifolia for TSS 73,78%; 77,18%; 84,71%; BOD5 85,83%; 90,33%; 94,17%; COD 86,94%; 90,65%; 94,87%; Ammonia 76,07%; 84,25%; 87,52%; sulfide 94,56%; 99,18%; 99,81 %.